Analysis of Biogas Potential Based on Land Carrying Capacity and Livestock to Support Household Energy Transition in Cirahab Village, Lumbir Subdistrict, Banyumas Regency - Rahmah Dwilestari; Rudi Laksomo; Yanda Dwira Firman Z (International journal of technology and education research, 2026)
The development of cattle-based biogas is one alternative for supporting rural energy security and reducing dependence on subsidized LPG. This study aims to analyze land carrying capacity, cattle stocking rates, and the potential for LPG subsidy savings in Cirahab Village, Banyumas Regency. The method used was quantitative descriptive analysis with five land-use scenarios (10-50%) of the village’s total area of 946 ha. The results of the analysis show that the land’s carrying capacity can accommodate 946-4,730 head of cattle, which has the potential to meet the energy needs of 378-1,892 households. Under a 40% land-use scenario, the livestock capacity reaches 3,784 head of cattle with biogas production of approximately 35,119 m³ per month, equivalent to 5,385 3-kg LPG cylinders. Assuming an LPG subsidy of Rp30,000 per cylinder, this program has the potential to save the government approximately Rp161.55 million per month, or Rp1.94 billion per year, in subsidy expenditures. The study’s findings indicate that the development of cattle-based biogas has the potential to support community energy self-sufficiency while improving the efficiency of government energy subsidies.